Lower Experiential Avoidance Is Associated With Psychological Well-being and Improved Cardiopulmonary Endurance Among Patients in Cardiac Rehabilitation. Issue 6 (November 2016) - Goodwin, Christina L.; Emery, Charles F.
Abstract : PURPOSE: Patients with a diagnosis of cardiac disease are often asked to make significant lifestyle changes, but they may experience difficulty initiating and maintaining lifestyle changes, especially when engaging in experiential avoidance (EA), the tendency to push away unpleasant emotions and sensations. This study examined the relationship between EA, psychological functioning, cardiac-quality of life (cardiac-QOL), program adherence, and cardiopulmonary endurance among patients entering an outpatient cardiac rehabilitation (CR) program. METHODS: Patients completed study questionnaires pre-CR, including 2 measures of EA (general and cardiac-specific), and assessments of psychological functioning and cardiac-QOL. Adherence was calculated as the proportion of insurance-approved CR sessions attended. Thirty participants completed stress testing pre-CR and post-CR. RESULTS: Forty-seven patients completed the questionnaires. General EA was associated with greater depression ( r = 0.73, P < .001), anxiety ( r = 0.56, P < .001), and stress ( r = 0.65, P < .001) and lower cardiac-QOL ( r =−0.69, P < .001). In addition, when controlling for the influence of general EA, greater cardiac-specific EA was associated with depression ([INCREMENT] R 2 = 0.05, P = .01), anxiety ([INCREMENT] R 2 = 0.18, P < .001), and poorer cardiac-QOL ([INCREMENT] R 2 = 0.04, P = .04). However, lower cardiac-specific EA predicted greater increases in cardiopulmonary endurance ( O2peak ) during the CR program ( b =−0.18, P = .002; [INCREMENT]adjusted R 2 = 0.07). Experiential avoidance was not associated with adherence. CONCLUSIONS: Lower EA is associated with better psychological well-being among patients entering a CR program and with better exercise outcomes. Strategies for reducing EA may be important to consider in future clinical studies. Abstract : Experiential avoidance (EA), the tendency to push away unpleasant emotions and sensations, was evaluated among cardiac rehabilitation (CR) patients. Greater general and cardiac-specific EA at program entry was associated with poorer psychological functioning and poorer cardiac-quality of life. In addition, lower cardiac-specific EA predicted greater increases in cardiopulmonary endurance during CR.